The Emergence of New Regional Health Diplomacyin Post-Neoliberal Times: The Case of UNASUR Health - Herrero, María Belén (2014)
Since the creation of Union of South American Nations (UNASUR), health policies have become a strategic element in dealing with the impact of neoliberal policies in the region. The aim of this paper is: first, to describe the social, political and economic processes that explain the emergence of UNASUR and its focus on social policy through health care, and second, how through UNASUR Health, health became the engine behind a new kind of health diplomacy. This article hopes to contribute to the debate on the new forms of health diplomacy and the role of regional organizations concentrating on health policies as a centrepiece of their regional integration efforts and the reduction of social inequalities.